The Phenomenon of Public Spending Growth in the Libyan Economy: Exploring the Causes - بدر, د. حسن الدامي (Dirasat in Economics and Business, 2022)
A phenomenon that has be-come familiar in almost all the economies of the countries of the world is the trend towards the size of public spending and its share of GDP to increase through time. Understanding the causes of this phenomenon has been one of the main concerns of pubic economists and finan-ciers, and exploring the most important economics has beco-me the focus of many studies and experimental research.The study explores, using the econ-ometric methodology, the main reasons for the growth in the size of public spending and its share of GDP in Libyan econ-omy during the period. (1962-2014), The results revealed that increased oil revenues, the deg-ree of economic openness, inf-lation and decreased average per capita GDP were causes of this phenomenon in Libyan econ-omy over the long run.